RELASI MANUSIA DENGAN LINGKUNGAN DALAM KUMPULAN CERPEN DANAU SEMBULUH KARYA MUHAMMAD YASIR: KAJIAN EKOKRITIK GLOTFELTY - Syahri Ramadhani; Nensilianti Nensilianti; Suarni Suarni (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
The purpose of this study is to describe the relationship between humans and the environment and factors that influence the relationship between humans and the environment. This research is descriptive qualitative. Data collection technique is documentation technique that is reading and recording data in accordance with the focus of research. This research was conducted by identifying, classifying, and analyzing data in the collection of Danau Sembuluh short stories by Muhammad Yasir. The results showed that in the collection of Danau Sembuluh short stories, the author gave rise to the environmental wisdom values ​​of the Ngaju Dayak tribe in the form of an attitude of respect for nature, an attitude of responsibility towards nature, the principle of love and care for nature, an attitude of not harming nature, and the principle of simple and harmonious living. with nature. The factors that influence human relations with the environment are religion, economics, technology, and education. Keywords: relations, ecological wisdom, short stories, ecocritics